Jewish Women in Europe in the Middle Ages a quiet revolution - Gôldîn, Śimḥā 1955- (Gender in history, 2011)
"The social structure of medieval Jewry was dominated by men who did not regard women as sharing equal status, and who took responsibility for the entire community, women included. This leadership sought to strengthen the family, the backbone of Jewish society, while attempting to improve their security within the Christian society which was seeking to displace them. However, this wider aim required improvement in status for women, which would provoke internal opposition within the Jewish community. Goldin's study depicts a social conflict within a community, a conflict that was gender oriented, but primarily social in nature. The twelfth century witnessed fundamental changes in the status of Jewish women in terms of their relationships with their husbands and within the family. The prohibiting of polygamy and divorce without the woman's consent gave rise to a quiet revolution. This engaging study looks closely at the changing attitudes towards women and the changes in her social status. Goldin highlights the case of Licoricia of Winchester, who in 1240 married David of Oxford, one of the wealthiest Jews in England - a moneylender whose clients included the King himself. Licoricia was very active with her husband in their joint enterprises. Four years after their marriage, David died leaving her with so vast a fortune that a royal decree was issued for her arrest and she was placed in the Tower of London. Using original Hebrew sources, this engaging study explores the relationships between men and women within Jewish society and the examinable factors in the functioning of community."--Publisher's website